Regulasi Komunikasi Antar Pribadi dan Strategi Komunikasi Perubahan Perilaku terkait Upaya Pencegahan Stunting di Kabupaten Magetan, Jawa Timur: Action Research - Ulfa Al Uluf; Sri Sumarmi; Setya Haksama (Media Gizi Kesmas, 2023)
Background: Stunting is a national priority. Some programs have been carried out including specific and sensitive nutritional interventions. This intervention program is an effort to accelerate the decline and prevention of stunting. Activities related to stunting prevention have been held, but in the process of planning and budgeting, implementation, monitoring, to evaluation are still experiencing obstacles. so that the process of torture until the evaluation can run well. The preparation of this strategy is done to improve the scope and quality of nutritional services. The National Strategy for The Acceleration of Stunting Prevention consists of five pillars. The second pillar of the National Strategy for The Acceleration of Stunting Prevention is the National Campaign and communication of behavior change. As the embodiment of pillar 2 of the National Strategy for The Acceleration of Stunting Prevention, each region must have a draft regulation and Communication Strategy Document. But in fact there are some districts / cities that do not have regulations and communication strategies related to stunting prevention, one of which is Magetan. Therefore, assistance is carried out in the draft drafting of Regulations and Communication Strategy Documents. Objectives: in order to be able to prepare Draft Regulations and communication strategies for changes for stunting prevention in Magetan Regency. Methods: The method in this activity is to assist in the implementation of the Draft Regulation and Communication Strategy Document of behavior change in efforts to prevent Stunting with this method of mentoring using PAR (Participatory Action Research). Results: The assistance activities of drafting KAP regulations and behavior change communication strategy documents in efforts to prevent stunting in Magetan Regency are carried out through several stages, namely: the implementation of mentoring and follow up of the results of mentoring. Mentoring is carried out 3 times from each activity both online and offline.  then followed up the results of the assistance presented then given input for the improvement of the draft communication between personal and behavioral change communication strategies that have been made during mentoring. Conclusions: Mentoring activities in the preparation of regulations resulted in a draft of KAP Regulation "Acceleration of Integrated Stunting Reduction and Prevention in Magetan Regency", addition of The Communication Strategy of Behavior Change paragraph 6 article 11 in the second section on the preparation of the activity plan 8 convergence actions.  The Preparation of Strategy documents resulted in a draft document of Behavioral Communication Strategy in accelerating stunting prevention. The finalization and determination of Dokement Strakom was carried out in Magetan in December 2021 by the Regional Secretary of Magetan Regency.